2022
DOI: 10.3390/biomedicines10020467
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Metabolic State and Fetal Sex and Genotype Modulate Methylation of the Serotonin Receptor Type 2A Gene (HTR2A) in the Human Placenta

Abstract: The serotonin receptor 2A gene (HTR2A) is a strong candidate for the fetal programming of future behavior and metabolism. Maternal obesity and gestational diabetes mellitus (GDM) have been associated with an increased risk of metabolic and psychological problems in offspring. We tested the hypothesis that maternal metabolic status affects methylation of HTR2A in the placenta. The prospective study included 199 pairs of mothers and healthy full-term newborns. Genomic DNA was extracted from feto-placental sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
2
10
2
Order By: Relevance
“… No data on foetal sex Lu et al, 2022 [ 88 ] 80 GDM 119 Ctrl PS HTR2A Increased pre-pregnancy BMI and GDM was independently associated with lower promoter DNAm in female but not male placentas. Stratified for foetal sex Horvatiček et al, 2022 [ 89 ] 34 GDM 46 Ctrl PS LEP Higher DNAm in placenta from women with GDM of South Asian ethnicity but not European ethnicity. No data on foetal sex Sletner et al, 2021 [ 90 ] 33 GDM 27 Ctrl PS FTO No association between FTO DNAm and GDM.…”
Section: Introductionmentioning
confidence: 99%
“… No data on foetal sex Lu et al, 2022 [ 88 ] 80 GDM 119 Ctrl PS HTR2A Increased pre-pregnancy BMI and GDM was independently associated with lower promoter DNAm in female but not male placentas. Stratified for foetal sex Horvatiček et al, 2022 [ 89 ] 34 GDM 46 Ctrl PS LEP Higher DNAm in placenta from women with GDM of South Asian ethnicity but not European ethnicity. No data on foetal sex Sletner et al, 2021 [ 90 ] 33 GDM 27 Ctrl PS FTO No association between FTO DNAm and GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent study highlighted the association of reduced methylation levels in the promotor region of HTR2A in human placenta with higher body mass index and GDM. Additionally, this study shown a sex‐dependent difference in methylation pattern in HTR2A (Horvatiček et al, 2022) that may contribute to sex‐specific brain programming. Altogether, these methylation differences influencing the serotonin signaling pathway may lead to NDDs later in childhood.…”
Section: Modified Placental Methylation Patterns and Its Consequencesmentioning
confidence: 61%
“…It has also been reported that expression of serotonin receptor HTR2A is decreased in GDM placentas ( 80 ). Interestingly, DNA methylation of the placental HTR2A gene was associated with maternal overweight/obesity and GDM only in female, but not in male placentas ( 129 ).…”
Section: Serotonin System and Its Components In The Human Placentamentioning
confidence: 99%
“…The sexually dimorphic nature of the serotonin system in the human placenta is supported by the male-specific correlation of serotonin levels in placenta and fetal brain ( 65 ). In addition, methylation of the HTR2A gene in human placenta has been shown to be associated with maternal overweight/obesity only in female placentas ( 129 ), suggesting that fetal sex modulates the sensitivity of the placental serotonin system to the intrauterine environment. Furthermore, studies in animals and humans suggest an interaction between sex hormones and the serotonin system.…”
Section: Outlook - Future Perspectivesmentioning
confidence: 99%